Flood Mapping Due to Proposed Overtopping Failure of Al Bassel Dam - غندور رهام; مجد هيفا (Latakia University Journal -Engineering Sciences Series, 2023)
Climatic conditions are changing and flood occurrences are increasing in frequency and intensity. The world’s population is also becoming increasingly urban, meaning a flood could cause more damage than before. The flood may come as a result of the dams break, which causes huge losses in lives and property and severe damage to the infrastructure, as important areas and facilities are submerged. This study includes the analysis of the flood wave resulting from the break of Al-Bassel Dam in Tartous, using a one-dimensional hydraulic model HEC-RAS-1D and the HEC-GEORAS tool in the GIS program, which helps in extracting topographic data to the river from topographic maps, with the aim of drawing inundation maps to determine the affected areas with this wave. We predicted the breach parameters using the Froehlich equation (1995), and the introduction of the hydrograph of the design flood wave of the dam that passes every 10,000 years once as a boundary condition and simulate the break dam as a result of overtopping, the results showed that the greatest flow occurred fifty minutes after the start of the break Its value was 29606 m3/sec, and the velocity values ​​ranged between m/sec (3-26) along the stream. The results also showed that overtopping is the most dangerous scenario.